Cardiac dysfunction-induced by polymeric drug delivery systems can be rescued with adjunct use of cardioprotective agents - Akhtar, Saghir; Benter, Ibrahim (Wiley, 2023)
[Abstract Not Available]
19th World Congress of Basic and Clinical Pharmacology (WCP) -- JUL 02-07, 2023 -- Glasgow, SCOTLAND